GROWTH PERFORMANCE OF SNAKESKIN GOURAMI, TRICHOGASTER PECTORALIS (REGAN, 1910) THROUGH WEANING STRATEGIES - SANGIPRAN BAISHYA,; K. KALITA,; , B. PHUKAN,; M. P. DUTTA,; R. BORDOLOI, (The Bioscan, 2012)
For successful venture in ornamental fish seed production proper nourishment at different life stages holds the key. Growth and survival of fry of snakeskin gourami, Trichogaster pectoralis by using mixed zooplankton and formulated feed was evaluated during this study. Fry of snakeskin gourami, Trichogaster pectoralis was weaned from mixed zooplankton to formulated feed. Snakeskin gourami, Trichogaster pectoralis fry (1.6 ± 0.06cm initial length and 0.39 ± 0.003g initial body weight) were fed with mixed zooplankton (T1) and formulated feed (T2), and combination of both live food and formulated feed in case of weaning treatments i.e. weaning at day 6 (T3), the reduction in quantity of mixed zooplankton were performed at day 2, 4 and 6. Similarly for weaning treatment T4 (weaning at day 12), these changes were made at day 6, 9 and 12 and for weaning treatment T5 (weaning at day 24) at day 12, 18 and 24. The fish weaned at day 24 (T5) had the highest average length gain and differed significantly (p < 0.05) from fry fed mixed zooplankton (T1). In case of average weight gain, specific growth rate and survival fry weaned at day 24 were highest and differed significantly (p < 0.05) from fry fed mixed zooplankton (T1), formulated feed (T2) and combination of both live food and formulated feed (T3 and T4). This study showed that replacement of mixed zooplankton by formulated feed at day 24 i.e. late weaning appears feasible. The fry weaned at day 24 (T5) showed significant increase in growth and survival from initial stocking i.e. 3.65 ± 0.13cm length, 0.85 ± 0.01g weight and 97.50 ± 2.50% survival respectively.